Hubungan Regulasi Diri dengan Prestasi Belajar Kalkulus II Ditinjau dari Aspek Metakognisi, Motivasi dan Perilaku - Hidayat, Akhmad Faisal (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
This research aimed to analyze the relationship between self regulation according to three its compiler aspect, that are metacognition, motivate and behavioral with learn achievement of 2nd calculus. The samples in this research are students of mathematic’s program study year 2012nd that programming subject of 2nd calculus with 59 students. The Data obtained from metacognition’s scale, motivate’s scale, behavioral’s scale and documentation final assess of 2nd calculus lesson. The data were analyzed by analysis correlation. Result show that: (1) there is very significantly positive correlation between metacognition and learn achievement of 2nd calculus (r = 0,743; = 0,05); (2) there is very significantly positive correlation between motivate and learn achievement of 2nd calculus (r = 0,791; = 0,05); (3) there is very significantly positive correlation between behavioral and learn achievement of 2nd calculus (r = 0,895; = 0,05); (4) there is very significantly positive correlation between metacognition, motivate and behavioral by simultan with learn achievement of 2nd calculus (R = 0,778; = 0,05). The conclusion that, self regulation according to metacognition, motivate and behavioral owning significantly correlation with somebody learn achievement, specially for 2nd calculus subject.